Victorious French after the siege of Rouen in 1449 (engraving, c. 1867) - A. Burgun (Wikimedia Commons, 1867)
Notice iconographique issue de Wikimedia Commons. Titre: Victorious French after the siege of Rouen in 1449 (engraving, c. 1867). Victorious French after the siege of Rouen in 1449 (engraving, c. 1867)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie